Invisible and Silent Along the Blue Highways - Patricla A. Schmuck (Educational Considerations, 1995)
If you are to achieve equal educational opportunities, you as educational leaders, must be the people who confront the stereotypes: you must be the leaders who deliver the rhetoric of equality.